Feminist Crisis Perspective: Between Exploitation and Politicisation - Matteo Codelupi (Athena)
Starting from a short reconstruction of the ongoing social reproduction crisis, with this article proposal we present an analysis that aim to investigate the close connection between globalisation and reorganisation of the patriarchal domination, that set out the social reproduction (and the reproductive work) as a crucial research ground to comprehend the current extensive and subjective process of both capital and labour. Specifically, we want to focus on two mutually dependent elements of analysis. Firstly, we will try to investigate the methods of operation through which the extractivism and the neoliberalism take root on the social reproduction, as “body-territory” of the crisis, that reconfigures the dispossession’s and the exploitation’s shape itself. Secondly, we want to remark the feminist and directly political character of the social reproduction as a common ground of departure, clash and conflict between capital and “potencia feminista”, that opens up to interesting scenarios to rethink the shapes of commons life.